A meta-analysis of effectiveness of interventions to improve adherence in pregnant women receiving antiretroviral therapy in sub-Saharan Africa. (September 2018) - Omonaiye, Olumuyiwa; Nicholson, Pat; Kusljic, Snezana; Manias, Elizabeth
Highlights: Living with human immunodeficiency virus (HIV) is a major health problem for pregnant women in sub-Saharan Africa. Multiple combination interventions demonstrated significant improvement in adherence in pregnant women receiving ART. The use of device reminder independently demonstrated significant improvement in adherence in pregnant women receiving ART. The perspectives of patients, caregivers and health care workers are needed to develop tailored and sustainable interventions. Abstract: Objective: We evaluated the effectiveness of interventions aimed at improving antiretroviral therapy (ART) adherence during pregnancy in sub-Saharan Africa. Methods: For this meta-analysis, the following databases were searched: MEDLINE Complete, Embase, Global Health, CINAHL Complete, and Google Scholar. Randomized and nonrandomized studies were considered for inclusion if they involved an intervention with the intent of improving medication adherence among pregnant women taking ART in sub-Saharan Africa. Databases were searched from inception to the end of August 2017. The primary outcome assessed was adherence to ART, defined as the proportion of women adherent to treatment in the control and intervention groups. Risk ratios and random effect meta-analysis were undertaken, and heterogeneity was examined with the I 2 statistic. Results: The systematic search of databases yielded a total of 402 articles, of which 19 studies were selected for meta-analysis with a total of 27, 974 participants. Nine types of interventions were identified in the 19 studies to improve ART adherence. The test for the subgroup differences showed that there was a statistically significant difference among the 9 subgroups of interventions, χ 2 (8) = 102.38; p = 0.00001. Collectively, in the meta-analysis, the various intervention types made a significant impact on improving medication adherence. The overall effect estimate with 95% CI was as follows: 1.25 (95% CI = 1.03, 1.52, p = 0.03). The following risk ratio results for meta-analysis were obtained for the three interventions that showed significant impact on adherence; namely social support and structural support, 1.58 (95% CI = 1.36, 1.84, p < 0.00001); education, social support and structural support = 2.60 (95% CI = 1.95, 3.45, p < 0.00001); and device reminder = 1.13 (95% CI = 1.05, 1.20, p = 0.0004). The proportion of women who were adherent to ART as a result of the interventions was 59.3% compared with 22.5% in the control groups. Conclusion: The use of device reminder, a combination of social support and structural support, and education, social support and structural support has the potential to improve ART adherence during pregnancy. Good quality prospective observational studies and randomized control trials are needed in sub-Saharan Africa to determine the most effective interventions.